COMMUNITY PARTICIPATION IN THE DEVELOPMENT PROGRAM WHICH IS ASSUMED FROM THE ALLOCATION OF VILLAGE FUNDS: Array - Wahyu Hidayat; Aan Anwar Sihabudin (JGSRD: Journal of Government Science and Rural Development, 2020)
This research is motivated by the low role of the community in helping and working together during the implementation of the development program, and the low awareness of the community towards the development program that is carried out. The research method used is descriptive analysis method using qualitative, data collection techniques with observation, interviews and literature studies. The data analysis technique uses three steps, namely data reduction, data presentation and concluding/verification. Community Participation in Development Programs Sourced from the Village Fund Allocation in Bantarmangu Village, Cimanggu District, Cilacap Regency in general has been running, but its implementation is still less than optimal, this can be supported by the still lack of cooperation and self-help in the form of material in the implementation of development, and still the existence of development results that have not been properly maintained and utilized. Community awareness, concern and trust in village government is still very low, and there is also no social closeness between the village government and the community. Besides there is no budget from the village government for the activities of the development budget and the program that has not been implemented. The village government has agreed to deliver information on village development activities by door to door and through loudspeakers, conducting development evaluation meetings every three months starting from the hamlet to the village level, encouraging development from non-government organizations and assisting community service in each hamlet.